IL-36R signalling activates intestinal epithelial cells and fibroblasts and promotes mucosal healing in vivo - Scheibe, Kristina; Backert, Ingo; Wirtz, Stefan; Hueber, Axel; Schett, Georg; Vieth, Michael; Probst, Hans Christian; Bopp, Tobias; Neurath, Markus; Neufert, Clemens (Gut, 2016)
Interleukin (IL)-36R signalling plays a proinflammatory role in different organs including the skin, but the expression of IL-36R ligands and their molecular function in intestinal inflammation are largely unknown.We studied the characteristics of IL-36R ligand expression in IBDs and experimental colitis. The functional role of IL-36R signalling in the intestine was addressed in experimental colitis and wound healing models in vivo by using mice with defective IL-36R signalling (IL-36R-/-) or Myd88, neutralising anti-IL-36R antibodies, recombinant IL-36R ligands and RNA-seq genome expression analysis.Expression of IL-36? and IL-36? was significantly elevated in active human IBD and experimental colitis. While IL-36? was predominantly detected in nuclei of the intestinal epithelium, IL-36? was mainly found in the cytoplasm of CD14(+) inflammatory macrophages. Functional studies showed that defective IL-36R signalling causes high susceptibility to acute dextran sodium sulfate colitis and impairs wound healing. Mechanistically, IL-36R ligands released upon mucosal damage activated IL-36R(+) colonic fibroblasts via Myd88 thereby inducing expression of chemokines, granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-6. Moreover, they induced proliferation of intestinal epithelial cells (IECs) and expression of the antimicrobial protein lipocalin 2. Finally, treatment of experimental intestinal wounds with IL-36R ligands significantly accelerated mucosal healing in vivo.IL-36R signalling is activated upon intestinal damage, stimulates IECs and fibroblasts and drives mucosal healing. Modulation of the IL-36R pathway emerges as a potential therapeutic strategy for induction of mucosal healing in IBD.
EVALuna2:2028

Loss of Survivin in Intestinal Epithelial Progenitor Cells Leads to Mitotic Catastrophe and Breakdown of Gut Immune Homeostasis - Martini, Eva; Wittkopf, Nadine; Günther, Claudia; Leppkes, Moritz; Okada, Hitoshi; Watson, Alastair J.; Podstawa, Eva; Backert, Ingo; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph (Cell Reports, 2016)
A tightly regulated balance of proliferation and cell death of intestinal epithelial cells (IECs) is essential for maintenance of gut homeostasis. Survivin is highly expressed during embryogenesis and in several cancer types, but little is known about its role in adult gut tissue. Here, we show that Survivin is specifically expressed in transit-amplifying cells and Lgr5(+) stem cells. Genetic loss of Survivin in IECs resulted in destruction of intestinal integrity, mucosal inflammation, and death of the animals. Survivin deletion was associated with decreased epithelial proliferation due to defective chromosomal segregation. Moreover, Survivin-deficient animals showed induced phosphorylation of p53 and H2AX and increased levels of cell-intrinsic apoptosis in IECs. Consequently, induced deletion of Survivin in Lgr5(+) stem cells led to cell death. In summary, Survivin is a key regulator of gut tissue integrity by regulating epithelial homeostasis in the stem cell niche.
EVALuna2:2058

STAT3 Activation in Th17 and Th22 Cells Controls IL-22-Mediated Epithelial Host Defense during Infectious Colitis - Backert, Ingo; Koralov, Sergei B.; Wirtz, Stefan; Kitowski, Vera; Billmeier, Ulrike; Martini, Eva; Hofmann, Katharina; Hildner, Kai; Wittkopf, Nadine; Brecht, Katrin; Waldner, Maximilian; Rajewsky, Klaus; et al. (Journal of Immunology, 2014)
The Citrobacter rodentium model mimics the pathogenesis of infectious colitis and requires sequential contributions from different immune cell populations, including innate lymphoid cells (ILCs) and CD4(+) lymphocytes. In this study, we addressed the role of STAT3 activation in CD4(+) cells during host defense in mice against C. rodentium. In mice with defective STAT3 in CD4(+) cells (Stat3(?CD4)), the course of infection was unchanged during the innate lymphoid cell-dependent early phase, but significantly altered during the lymphocyte-dependent later phase. Stat3(?CD4) mice exhibited intestinal epithelial barrier defects, including downregulation of antimicrobial peptides, increased systemic distribution of bacteria, and prolonged reduction in the overall burden of C. rodentium infection. Immunomonitoring of lamina propria cells revealed loss of virtually all IL-22-producing CD4(+) lymphocytes, suggesting that STAT3 activation was required for IL-22 production not only in Th17 cells, but also in Th22 cells. Notably, the defective host defense against C. rodentium in Stat3(?CD4) mice could be fully restored by specific overexpression of IL-22 through a minicircle vector-based technology. Moreover, expression of a constitutive active STAT3 in CD4(+) cells shaped strong intestinal epithelial barrier function in vitro and in vivo through IL-22, and it promoted protection from enteropathogenic bacteria. Thus, our work indicates a critical role of STAT3 activation in Th17 and Th22 cells for control of the IL-22-mediated host defense, and strategies expanding STAT3-activated CD4(+) lymphocytes may be considered as future therapeutic options for improving intestinal barrier function in infectious coliti
EVALuna2:1843